The Nutritional and Phytochemical Composition of the Indigenous Australian Pindan Walnut (Terminalia cunninghamii) Kernels - Zhong, L.; Bornman, J.; Wu, G.; Hornoff, A.; Dovi, K.; AL-Ali, H.; Aslam, N.; Johnson, Stuart (Springer, 2017)
© 2017 Springer Science+Business Media, LLC, part of Springer Nature Nutritional composition of the kernels of two types of Pindan walnut (Terminalia cunninghamii), a native nut consumed traditionally by Australian Indigenous peoples, is reported for the first time. Results showed that Pindan walnut kernels contained high levels of fat, protein and ash, approximately 50, 30 and 5% fresh basis, respectively. The levels of minerals in the kernels were much higher than common walnuts and macadamia nuts, especially those of phosphorus, magnesium and zinc. The high amounts of polyphenols in the kernels provided strong hydrophilic antioxidant capacities, of up to 2004 mg Trolox equivalents/100 g fresh basis using the hydrophilic oxygen radical absorbance capacity assay. Both free polyphenol content and hydrophilic antioxidant capacities of the kernels were higher than those of macadamia nuts, although the lipophilic oxygen radical absorbance capacity was lower. These preliminary studies indicate high potential for wider use of the Pindan walnut as a novel, nutritious and health-promoting food.